Validation of the inventory: lockdown and its impact on the university Community - María Yolanda González-Alonso; Andrea Liliana Ortiz-González; María Camino Escolar-Llamazares; Diego Serrano-Gómez; Isabel Serrano-Pintado; María Ángeles Martínez-Martín (BMC, 2024)
Abstract Background Significant consequences of COVID-19 within academic/professional life are, at the psychological level, related to worry, tension, stress; coping strategies and lifestyle changes. This study describes the process of design and validation of an inventory (QPIC), which aims to assess the psychological impact that a situation of confinement can produce among university students and teachers. Methods Design of the instrument and psychometric tests. A sample of 862 students and 229 professors affiliated to Spanish and Colombian universities was used. Data were collected in April 2020 with the request of the favourable Bioethics Committee IR/2020. Results Six experts carried out the content validation. A confirmatory factor analysis of the theoretical dimensions proposed for the scales was performed and the internal consistency of each of the three initial scales was confirmed (0.866, 0.813 and 0.834). Conclusion A rigorous and reliable instrument is achieved, consisting of two final scales: (a) Worry, tension and stress scale (b) Coping scale, which helps to measure individual psychological effects in housebound situations. It is an instrument designed, constructed ad hoc to assess the impact of confinement and subjected to validation. The factor structure and reliability of the instrument are examined and good psychometric properties are obtained. The application of this inventory will make it possible to assess the impact on people's mental health during a period of confinement.